STRATEGIC DIAGNOSTICS IN THE LANGUAGES OF GLOBAL CHANGE FROM THE WORLD OF VOCA TO BANI - IGNATIEVA, Iryna; SERBENIVSCA, Alina; IHNATIEV, Olexsandr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article analyzes the specifics of changes in the strategic diagnostics of business entities in the context of global changes in the world of transition from the VOCA to the BANI management model.  The methodological apparatus of strategic diagnostics, which was used in the conditions of the assumed SPOD world, is analyzed.  It is found that, in general, SPOD methods remain relevant for traditional industries or organizations in relatively stable conditions, but have limitations in terms of application in conditions of high instability or rapid market change. Traditional methods of strategic diagnostics, such as SWOT analysis, PEST analysis, and benchmarking, often do not solve the strategic tasks that management faces when justifying strategic decisions.   It has been found that BANI (Brittle, Anxious, Nonlinear, Incomprehensible) methods are used in the modern world with a high level of fragility of systems, anxiety of process participants, nonlinearity of processes and incomprehensibility of situations.  In the BANI world, strategic diagnostics should take into account the peculiarities of this environment, so when developing it should include: determining the level of vulnerability of organizational systems to external shocks and developing strategies to increase their resilience, assessing the emotional state of employees and customers to reduce stress and increase motivation through the development of emotional intelligence, understanding the complex relationships between various business factors to predict unpredictable consequences of actions, identifying areas of activity where the lack of information ab Today, the problems of quantitative assessment and methodological support for the use of this methodology in strategic diagnostics have not yet been fully resolved.
Keywords: strategic diagnostics; strategic management; development; management system; global changes